PENGARUH UKURAN KAP, PERTUMBUHAN PERUSAHAAN DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN DENGAN KONDISI KEUANGAN SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun - anggreani, Arum septhia; Srimindarti, Ceacilia (2021)
Thissstudyyisstooexamine and analyzeethe effect of KAP size, company growth and previous year’s audit opinion on going concern audit opinion as moderated by the financial condition. The population used in this study is an manufactur company listed on the Indonesian Stock Exchange (IDX) with an observasion period of five years, namely 2016-2020. From the sample criteria that have been determided by the researcher, the resulting data is 280 samples of manufactur companies taken by purposive sampling technique, obtained from a number of 56 companies. This research is a quantitative study using secondary data from financial reporter annual reports published the website www.idx.co.id. Theehypothesisswasstasted byyusing logisticcregression analysis. The results indicate the the KAP size had a positive and significantteffectton the going concern audit opinion, company growth had a negative and significant effect on the going concern audit opinion, the previous year audit opinion have no effect on the going concern audit opinion. Financial condition is able to moderated company growth towards the acceptence of going concern audit opinion. While financial condition is not able moderated the KAP size and previous year audit opinion on the going concern audit opinion.